Effortful leisure is a source of meaning in everyday life - Aidan V. Campbell; Gregory J. Depow; Srishti Agarwal; Michael Inzlicht (Communications Psychology)
Abstract People derive much purpose from their work, yet time spent on work is decreasing. Here, we ask if effortful leisure is a powerful source of meaning and purpose that could supplement the reduction in labor time. In five studies (N = 2569), we investigated the relationship between effort and meaning in leisure activities. In Study 1 (N = 1145), we found that participants rated effortful activities as more meaningful, although less enjoyable, suggesting a trade-off between eudaimonic and hedonic wellbeing. Studies 2a (N = 375), 2b (N = 389), and 3 (N = 400) provided causal evidence by comparing effortful (Sudoku puzzling) and non-effortful leisure (watching videos in Studies 2a and 2b; Click-to-Reveal game in Study 3). Effortful activities consistently felt more meaningful, though the effects plateaued at higher levels of effort. Finally, Study 4 (N = 260) used experience sampling to assess activities as they occurred in real life. Effortful leisure fostered meaning while maintaining enjoyment, whereas other activities tended to feel less enjoyable with increased effort. Across all studies, we found that effort promotes meaningful experiences, particularly in leisure contexts, where effort does not diminish enjoyment. Effortful leisure may offer a powerful opportunity to supplement or replace the once plentiful purpose we derived from our now diminishing time at work.